Promoção da saúde bucal na estratégia saúde da família: do panorama nacional ao cotidiano de trabalho em áreas rurais - Paredes, Suyene de Oliveira (2023)
To comprehensively grasp the landscape of health promotion within the realm of oral health, encompassing both the national landscape of Oral Health Promotion (OHP) procedures and delving into more profound explorations of OHP practices at the local and regional levels, this study has formulated distinct objectives across three Planes of Analysis (PAs). PA 1 undertook an inquiry into the correlations between sociodemographic variables and municipal coverage provided by Family Health Strategy (FHS) in conjunction with OHP procedures across Brazil. This inquiry assumed the form of a cross-sectional investigation, leveraging secondary data sourced from the Ministry of Health, referring to 2019. Negative binomial regression models were employed to associate outcomes with covariates and to estimate the prevalence ratio (PR) along with corresponding 95% confidence intervals (95%CI). The analytical cohort encompassed 4,913 municipalities. The findings indicated that municipalities characterized by lower income inequality (PR=1.04; 95%CI 1.01-1.08), higher illiteracy rates (PR=1.06; 95%CI 1.00-1.13), and populations ranging from 10,001 to 50,000 inhabitants (PR=1.07; 95%CI 1.02-1.12), as well as populations ranging from 50,001 to 100,000 (PR=1.21; 95%CI 1.12-1.30), exhibited a heightened incidence of individual OHP procedures. Conversely, a reduced frequency was associated with lower susceptibility to poverty (PR=0.83; 95%CI 0.78-0.89) and diminished Oral Health Teams (OHT) coverage (PR=0.39; 95%CI 0.33-0.45). Regarding collective procedures, diminished frequency was correlated with lower income inequality (PR=0.91; 95%CI 0.87-0.95), lower HDI values (PR=0.53; 95%CI 0.35-0.80) for both low and medium HDI levels (PR=0.79; 95%CI 0.71-0.87), and lower per capita income (PR=0.84; 95%CI 0.81-0.88). PA 2 delved into an examination of the nexus between sociodemographic and professional profiles, coupled with work-related factors, and the effectiveness of OHP strategies. This phase of investigation adopted a cross-sectional, quantitative, descriptive, and analytical framework. The study cohort comprised 211 dentists selected through snowball sampling, all of whom were affiliated with OHT operating in Paraíba. Data were collected through a virtual questionnaire. To assess the effectiveness of OHP strategies, we employed a matrix encompassing health promotion values and pillars. The data were analyzed using Poisson Regression. Results were considered significant at p<0.05. Enhanced effectiveness of OHP strategies was notably linked with OHTs classified as "mixed" (urban and rural xi coverage area) (RP=1.54; 95%CI 1.154-2.076), where dentists held temporary contracts (RP=1.67; 95%CI 1.240-2.250). PA 3 aimed to achieve an in-depth comprehension of the activities of FHS dentists operating within rural OHTs in Paraíba, particularly from the standpoint of OHP and their daily responsibilities. Adopting a qualitative approach, this phase of investigation encompassed interviews with fourteen professionals. Thematic content analysis was employed as the methodology to understand and systematize the gathered data. The narratives emerging from this analysis unveiled imprecise conceptualizations of Health Promotion, wherein the scope of these concepts was often confined to the prevention of oral diseases. Disparities were evident regarding support units, and certain rural populations were devoid of specialized oral health services. Noteworthy engagement in outreach practices and initiatives targeting pregnant women was observed among professionals. However, the establishment of cohesive groups faced challenges, and intersectoral actions primarily revolved around collaborations between the healthcare and education domains. Discrepancies were evident in terms of managerial support. The narratives underscored the potential of OHP endeavors to bolster self-esteem and enhance quality of life, premised upon principles of comprehensive care, solidarity, and humanization. Positive sentiments were associated with the significance of their work and the favorable interactions with communities. These professionals encountered adversities encompassing socioeconomic and emotional requisites, geographical remoteness, infrastructural limitations, disparities in accessibility and organization, and complexities in harmonizing collective and individual initiatives. The biomedical care model and dental extractions were ingrained within the rural context, while dissatisfactions were attributed to remuneration and infrastructure. In summation, the municipal sociodemographic variables (income inequality, illiteracy populations ranging, susceptibility to poverty, HDI and per capita income) and OHT/FHS coverage influence the performance of OHP procedures in Brazil. In the Paraíba, greater effectiveness of OHP strategies can be influenced by professionals who work in urban and rural areas and with temporary contracts. In understanding the rural territories of Paraíba, the singularities of these locations result in challenges for OHP practices and the daily work of dentists.